Pantothenate kinase 4 controls skeletal muscle substrate metabolism - Adriana Miranda-Cervantes; Andreas M. Fritzen; Steffen H. Raun; Ondřej Hodek; Lisbeth L. V. Møller; Kornelia Johann; Luisa Deisen; Paul Gregorevic; Anders Gudiksen; Anna Artati; Jerzy Adamski; Nicoline R. Andersen; et al. (Nature Communications, 2025)
Abstract Metabolic flexibility in skeletal muscle is essential for maintaining healthy glucose and lipid metabolism, and its dysfunction is closely linked to metabolic diseases. Exercise enhances metabolic flexibility, making it an important tool for discovering mechanisms that promote metabolic health. Here we show that pantothenate kinase 4 (PanK4) is a new conserved exercise target with high abundance in muscle. Muscle-specific deletion of PanK4 impairs fatty acid oxidation which is related to higher intramuscular acetyl-CoA and malonyl-CoA levels. Elevated acetyl-CoA levels persist regardless of feeding state and are associated with whole-body glucose intolerance, reduced insulin-stimulated glucose uptake in glycolytic muscle, and impaired glucose uptake during exercise. Conversely, increasing PanK4 levels in glycolytic muscle lowers acetyl-CoA and enhances glucose uptake. Our findings highlight PanK4 as an important regulator of acetyl-CoA levels, playing a key role in both muscle lipid and glucose metabolism.